DNA methylation modification in Idiopathic pulmonary fibrosis - Ren, Lu; Chang, Yan-Fen; Jiang, Shi-He; Li, Xiao-Hong; Cheng, Hai-Peng (Frontiers in Cell and Developmental Biology, 2024)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, and irreversible interstitial lung disease with a prognosis worse than lung cancer. It is a fatal lung disease with largely unknown etiology and pathogenesis, and no effective therapeutic drugs render its treatment largely unsuccessful. With continuous in-depth research efforts, the epigenetic mechanisms in IPF pathogenesis have been further discovered and concerned. As a widely studied mechanism of epigenetic modification, DNA methylation is primarily facilitated by DNA methyltransferases (DNMTs), resulting in the addition of a methyl group to the fifth carbon position of the cytosine base, leading to the formation of 5-methylcytosine (5-mC). Dysregulation of DNA methylation is intricately associated with the advancement of respiratory disorders. Recently, the role of DNA methylation in IPF pathogenesis has also received considerable attention. DNA methylation patterns include methylation modification and demethylation modification and regulate a range of essential biological functions through gene expression regulation. The Ten-Eleven-Translocation (TET) family of DNA dioxygenases is crucial in facilitating active DNA demethylation through the enzymatic conversion of the modified genomic base 5-mC to 5-hydroxymethylcytosine (5-hmC). TET2, a member of TET proteins, is involved in lung inflammation, and its protein expression is downregulated in the lungs and alveolar epithelial type II cells of IPF patients. This review summarizes the current knowledge of pathologic features and DNA methylation mechanisms of pulmonary fibrosis, focusing on the critical roles of abnormal DNA methylation patterns, DNMTs, and TET proteins in impacting IPF pathogenesis. Researching DNA methylation will enchance comprehension of the fundamental mechanisms involved in IPF pathology and provide novel diagnostic biomarkers and therapeutic targets for pulmonary fibrosis based on the studies involving epigenetic mechanisms.